Psychosocial Experiences of Front-Line Nurses Working During the COVID-19 Pandemic in Hubei, China: A Qualitative Study - Wang, Jianjian; Zhong, Yaping; Ding, Jinfeng; Chen, Qiongni; Jiao, Jingjing; Huang, Chongmei (Frontiers in Public Health, 2022)
Background A large number of nurses across China joined the anti-coronavirus disease 2019 (COVID-19) front-line in Hubei province, where the local healthcare system faced unprecedented challenges in the early 2020. Few studies have reported the psychological experiences of nurses from other regions who voluntarily participated in the response to the COVID-19 pandemic in Hubei province. Aim To describe the psychological experiences of nurses who were involved in the anti-COVID-19 pandemic battle in Hubei province from January to April 2020. Methods This was a qualitative descriptive study using purposive and snowball sampling strategies for participant recruitment. Twenty-four nurses were approached and twenty-one of them completed telephone interviews in April 2020. The interviews took an average of 75 min (range 34–140 min). Data were analyzed thematically after verbatim transcription of the interviews. Results Our analysis generated three primary themes: (I) Contexts; (II) Psychological responses; and (III) Coping strategies (most participants identified suitable coping strategies including relaxing activities and seeking social support). Participants' psychological responses varied in four phases of the journey through the experience: (i) initiation phase: obligations and concerns/fears; (ii) transition phase: from overwhelmed to increased confidence; (iii) adaptation phase: a sense of achievement and exhaustion; and (iv) completion phase: professional and personal growth. Conclusion Nurses had concerns, fears, and faced challenges working on the COVID-19 front-line. However, they were motivated by a strong sense of professional commitment. Most nurses successfully achieved personal and professional growth as they identified a range of coping strategies. Future research is needed to explore the long-term impact of the COVID-19 related working experiences on these nurses.